Sensitive Determination of the Dissolved Phosphate Pool for an Improved Resolution of Its Vertical Variability in the Surface Layer: New Views in the P-Depleted Mediterranean Sea - Djaoudi, Kahina; Van Wambeke, France; Coppola, Laurent; D'Ortenzio, Fabrizio; Helias-Nunige, Sandra; Raimbault, Patrick; Taillandier, Vincent; Testor, Pierre; Wagener, Thibaut; Pulido-Villena, Elvira (Frontiers in Marine Science, 2018)
An accurate understanding of the biogeochemistry of dissolved phosphate pool in the upper waters of P-depleted oceanic regions is constrained by the low sensitivity of routine phosphate measurements. In this study, by using the sensitive Liquid Waveguide Capillary Cell method, we report the first extensive cross-basin survey of nanomolar dissolved inorganic phosphate (DIP) and dissolved organic phosphate (DOP) concentration in P-depleted surface waters of the Mediterranean Sea during the stratification period. In the north western Mediterranean Sea (NWMS), DIP above the mixed layer depth (MLD) ranged between 4.9 and 26.5 nM. Along an E-W transect crossing Ionian and Tyrrhenian Seas (E-W transect), DIP above the MLD was lower, ranging between 0.9 and 11.4 nM. Contrarily to the traditional view of a depleted and invariant surface dissolved phosphate pool, a significant vertical variability of DIP and DOP was revealed in upper waters. A positive gradient of DIP was observed above the phosphacline, between the MLD and the deep chlorophyll maximum (DCM) depth, suggesting a potential diffusion of new phosphate to near-surface waters, even under stratified conditions. Interestingly, despite this apparent DIP availability, a significant negative gradient of DOP concentration was observed in the same layer. Finally, the positive gradient in DIP coincided with a significant increase in N:P ratio, suggesting a higher rate of increase of N than of P. The results obtained in this study indicate that acquiring nanomolar DIP data is a sine qua non condition for the comprehension and prediction of the biogeochemical functioning of P-depleted oceanic regions, such as the Mediterranean Sea.